Hydrothermal conversion of lignocellulosic biomass to bio-oils - Gan, Jing (Kansas State University, 2012)
Corncobs were used as the feedstock to investigate the effect of operating conditions and crude glycerol (solvent) on bio-oil production. The highest bio-oil yield of 33.8% on the basis of biomass dry weight was obtained at 305°C, 20 min retention time, 10% biomass content, 0.5% catalyst loading. At selected conditions, bio-oil yield based on the total weight of corn cobs and crude glycerol increased to 36.3% as the crude glycerol/corn cobs ratio increased to 5. Furthermore, the optimization of operating conditions was conducted via response surface methodology. A maximum bio-oil yield of 41.3% was obtained at 280°C, 12min, 21% biomass content, and 1.56% catalyst loading. A highest bio-oil carbon content of 74.8% was produced at 340°C with 9% biomass content. A maximum carbon recovery of 25.2% was observed at 280°C, 12min, 21% biomass content, and 1.03% catalyst loading. The effect of biomass ecotype and planting location on bio-oil production were studied on big bluestems. Significant differences were found in the yield and elemental composition of bio-oils produced from big bluestem of different ecotypes and/or planting locations. Generally, the IL ecotype and the Carbondale, IL and Manhattan, KS planting locations gave higher bio-oil yield, which can be attributed to the higher total cellulose and hemicellulose content and/or the higher carbon but lower oxygen contents in these feedstocks. Bio-oil from the IL ecotype also had the highest carbon and lowest oxygen contents, which were not affected by the planting location. In order to better understand the mechanisms of hydrothermal conversion, the interaction effects between cellulose, hemicellulose and lignin in hydrothermal conversion were studied. Positive interaction between cellulose and lignin, but negative interaction between cellulose and hemicellulose were observed. No significant interaction was found between hemicelluose and lignin. Hydrothermal conversion of corncobs, big bluestems, switchgrass, cherry, pecan, pine, hazelnut shell, and their model biomass also were conducted. Bio-oil yield increased as real biomass cellulose and hemicellulose content increased, but an opposite trend was observed for low lignin content model biomass.
Keywords: Hydrothermal conversion; Lignocellulosic biomass; Bio-oil; Corn cob; Big bluestem; Energy (0791); Engineering, Agricultural (0539)